Estimating the option value of exercising risk-taking behavior with the hedonic market approach - Stefan Borsky; Paul A. Raschky (University of Innsbruck, Department of Public Finance, 2008)
Within the last decades an increasing number of people practice risky sports in their leisure time. Although there exists a vast number of economic literature on risk-taking behavior, an estimation of the individual willingness to pay (WTP) for the option to exercise risk-taking is missing. Monetarized values could support private industries in design pricing schemes that set incentives to reduce risk-taking behavior as well as public policy-makers to develop alternative instruments to reduce the adverse effects of risk-taking activity (e.g. accidents). We use data of 69 Austrian Ski resorts and 3,637 reported ski accidents and apply the hedonic market method. Our results suggest that the individual WTP for a hypothetical increase in the possibility to undertake risk-taking activities lies between 11% and 25% of the price of a ski-lift-ticket.
Keywords: D81; L8; Q51; 330; hedonic market approach; individual risk-taking; sports; Freizeitverhalten; Entscheidung bei Risiko; Unfall; Wintersport; Hedonischer Preisindex; Schätzung; Österreich